The Kazakhstan dairy enterprises’ problem analysis and innovative potential of an agricultural enterprise - Akhmedyarov, Y; Kurmanov, N; Petrova, M; Gordeyeva, Y (IOP conference series. Earth and environmental science, 2023)
In this study, the current situation in the agricultural sector of Kazakhstan and specifically the diary sphere is analized. Innovations and technologies for the dairy industry are also being researched, and the possibility of their utilization in Kazakhstan is proposed, along with ways to further agricultural development. This study shows the largest dairy enterprises of the Republic of Kazakhstan, their production capacities, and methods of milk production. It presents innovative methods that improve the process of milk production as well as its quality and quantity. This study reveals the problems of lack of acreage, absence of a clear subsidizing policy and state programs on supporting current and new industries, shortage of qualified personnel, and dependence on regulatory at both the national and transnational levels, etc. in the Republic of Kazakhstan in recent years. All these factors do not allow us to achieve adequately the required production rates, and with them comes the introduction of the latest technological methods in the production of dairy products. At the same time, there was an increase by 57.4% in the number of operating agricultural enterprises over the last 5 years, and the share of agriculture in the country’s GDP by 0.8-1%. The study shows the further ways of the innovative development of milk production, as well as the problems that these productions face and the ways to solve them.